A Robust Ethane-Trapping Metal-Organic Framework with a High Capacity for Ethylene Purification - Qazvini, Omid T; Babarao, Ravichandar; Shi, Zhao-Lin; Zhang, Yue-Biao; Telfer, Shane G (Journal of the American Chemical Society, 2019)
The separation of ethane from ethylene is of prime importance in the purification of chemical feedstocks for industrial manufacturing. However, differentiating these compounds is notoriously difficult due to their similar physicochemical properties. High-performance porous adsorbents provide a solution. Conventional adsorbents trap ethylene in preference to ethane, but this incurs multiple steps in separation processes. Alternatively, high-purity ethylene can be obtained in a single step if the adsorbent preferentially adsorbs ethane over ethylene. We herein report a metal-organic framework, MUF-15 (MUF, Massey University Framework), constructed from inexpensive precursors that sequesters ethane from ethane/ethylene mixtures. The productivity of this material is exceptional: 1 kg of MOF produces 14 L of polymer-grade ethylene gas in a single adsorption step starting from an equimolar ethane/ethylene mixture. Computational simulations illustrate the underlying mechanism of guest adsorption. The separation performance was assessed by measuring multicomponent breakthrough curves, which illustrate that the separation performance is maintained over a wide range of feed compositions and operating pressures. MUF-15 is robust, maintains its performance in the presence of acetylene, and is easily regenerated by purging with inert gas or by placing under reduced pressure.